Signaling Pathways Involved in Nutrient Sensing Control in Cancer Stem Cells: An Overview - Robles-Flores, Martha; Moreno-Londoño, Angela P.; Castañeda-Patlán, M. Cristina (Frontiers in Endocrinology, 2021)
A high proliferation rate is one of the hallmarks of cancer cells. Because tumor growth depends on energy-demanding anabolic processes, including biosynthesis of protein, lipid, and nucleotides, many tumor-associated conditions, including intermittent oxygen deficiency due to insufficient vascularization, oxidative stress, and nutrient deprivation, results from fast growth. To cope with these environmental stressors, cancer cells, including cancer stem cells, must adapt their metabolism to maintain cellular homeostasis. It is well- known that cancer stem cells (CSC) living in hypoxic niches reprogram their metabolism. They usually change from oxidative phosphorylation to increased aerobic glycolysis even in the presence of oxygen. However, as opposed to most differentiated cancer cells relying on glycolysis, CSCs can be highly glycolytic or oxidative phosphorylation-dependent, displaying high metabolic plasticity. Although the contribution of the metabolic and nutrient-sensing pathways to the maintenance of stemness has been recognized, the molecular mechanisms that link these pathways to stemness are not well known. Here in this review, we describe the most relevant signaling pathways involved in nutrient sensing and cancer cell survival. Among them, Adenosine monophosphate (AMP)-activated protein kinase (AMPK) pathway, mTOR pathway, and Hexosamine Biosynthetic Pathway (HBP) are critical sensors of cellular energy and nutrient status in cancer cells and interact in complex and dynamic ways.